EL HARAKAH : The Quest of the Islamic Archipelago InhertitanceThrough the Javanese Living Folklore - Siti Masitoh (UIN Maulana Malik Ibrahim, 2016)
Artikel ini bertujuan menggali warisan Nusantara islam melalui cerita rakyat orang jawa yaitu ruwatan.